Treatment pattern and outcomes of re-induction therapy prior to stem cell transplantation in patients with relapsed/refractory multiple myeloma in Germany - Sauer, Sandra; Engelhardt, Monika; Trautmann-Grill, Karolin; Kimmich, Christoph; Hänel, Mathias; Schmidt-Hieber, Martin; Salwender, Hans; Flossmann, Carmen; Heckmann, Hiltrud; Ertel, Franziska; Friederich, Andrea; Patel, Sachin; et al. (Bone marrow transplantation, 2024)
There are limited data guiding choice of re-induction therapies for patients with relapsed/refractory multiple myeloma (RRMM) prior to stem cell transplantation (SCT). We performed a retrospective medical chart review of 171 patients with RRMM in Germany who received re-induction therapy in second line (78%; n = 134) or third line (22%; n = 37) prior to re-SCT. Index therapy was defined as first completed re-induction therapy for planned myeloablative conditioning and SCT in second/third line within the eligibility period (1/2016-12/2019). Most common pre-index first line and maintenance therapy used were bortezomib-based combinations (91%; n = 155/171) and lenalidomide (55%; n = 29/53), respectively. Median duration of index therapy line was 9 months; carfilzomib-based combinations were the most widely used in second/third line re-induction therapy (49%; n = 83/171), followed by daratumumab-based combinations (21%; n = 36/171). Overall response rates in second/third line were 87% after re-induction and 96% after SCT; median time to next treatment line after start of index therapy was 31 months; median progression-free survival (PFS) was 29 months; and median overall survival after index date was not reached. Based on these data, re-induction therapy with salvage SCT appears to be beneficial in selected patients with RRMM in clinical practice in Germany, translating into deep responses, long PFS and prolonged time to next treatment.
Gesehen am 01.08.2024